Hubungan Self Awareness dan Kematangan Karir Siswa SMK “X” Blitar - Fortuna, Nirma Dewi; Bisri, Mohammad; Priyambodo, Aji Bagus; Hapsari, Ayu Dyah (Universitas Negeri Malang, 2022)
Abstract: The purpose of this study was to determine whether there is a relationship between self-awareness and career maturity of SMK